Analisa Kapasitas Saluran Drainase Pada Jalan Raya Kelet - Bangsri - khoirul mahfidh, muhammad; Roehman, Fatchur; Wibowo, Kartono (Jurnal Civil Engineering Study, 2022)
Drainage Jalan Raya Kelet - Bangsri, which is located in Jinggotan Village, Kembang District, Jepara Regency, is classified as an artificial drainage with a length of 725 meters. According to Muria News, “Jepara, 4/02/2020, it rained heavily from 10.30 to 15.00 on Jalan Raya Kembang - Bangsri, at that time there was a big flood which inundated the road as high as 30- 40 cm. Stagnant water occurs from the Flower Park to the Jinggotan bridge which is located to the south of SMA 1 Kembang. The flood disrupts the flow of local traffic, thereby inhibiting the speed of vehicles passing through it. "This research on the analysis of drainage capacity on Jalan Raya Kelet - Bangsri aims to determine the ability of drainage to drain wastewater, as well as to determine drainage capacity, and provide solutions to problems. the. In this previous research, what was done was to review the condition of the existing channel first, by collecting primary and secondary data then analyzing using HEC - RAS 5.0.7 software. Based on the problems that occurred on Jalan Raya Kelet - Bangsri drainage, it is necessary to analyze the drainage capacity, so that we can find out the solution for future planning. Hydrological analysis using HEC-RAS 5.0.7 software will make it easier to re-plan a drainage with a simulated channel condition. In the calculation analysis using the log distribution distribution log Pearson III because the value of Cs <1 from this method gets 2 years of rainfall 226.0757 mm, 5 years 285,6254 mm, 10 years 322,7451 mm so as to produce a planned flood discharge Q 2019 2.99 m3 / s, Q 2021 3.28 m3 / s, Q 2024 3.64 m3 / s, and Q 2029 4.04 m3 / s. whereas the HEC-RAS 5.07 software produces an average channel discharge of Q 2.43 m3 / s where Q Discharge> Q channel is stated that Q channel does not meet the requirements to drain flood discharge resulting in water runoff. For this reason, it is planned that U ditch with dimensions b = 1.2 m and h = 1.4 m with a manning roughness of 0.014 and a channel slope of 2.75%, from the analysis using HEC-RAS 5.0.7 software with U ditch dimensions b = 1.2 m and h = 1.4 m meet the requirements and are safe to accommodate flood discharge.